Using VISIR Remote Lab in the Classroom: Case of Study of the University of Deusto 2009-2019 - García-Zubía, Javier (2021)
During the last ten years, the University of Deusto is using VISIR remote lab for analog electronics in the Faculty of Engineering. Present paper shows how we are using the VISIR with students, and its results. It is a catalog of experiments to invite other universities to join the VISIR consortium. Ongoing and future research in VISIR are also presented